Pongkor Reveals : Characterization of Late Tertiary Au-Ag Ephitermal Low Sulphidation Deposits - Hady, Muhammad Husein Mubarak; Aulia, Fahmi; Pratama, Arisa Wahyu (2019)
Pongkor Ancient Volcano is one of tertiary volcano in Java which has been proven producing commodity of 98 tons Au and 1026 tons Ag (Milesi, 1999). The Au-Ag deposit in Pongkor is an interesting object for explorationist that needs to be studied and published in order to developing knowledge. The research was in one of the active mining area in Bantar Karet Village, Nanggung, Bogor, West Java in the UTM 48S zone with coordinates X: 672972mE-673373mE and 9263348mN-9262533mN. The purpose of this study was to determine the characteristics of Au-Ag deposits including geological settings, alteration distribution, and vein infilling. The research methods included surface mapping, face mapping in underground mining, and laboratory analysis such as petrography and geochemistry (XRD and Fire Assay). Based on surface mapping, there were 3 units of rock from old to young in the form of lapilli-tuff Pongkor unit, andesite volcanic Pongkor unit, and tuff Pongkor unit. All of them have miocene age. The structure that controls mineralization is right slip fault with NW-SE orientation. Based on XRD analysis, alteration that is present in the study area are phylic type (silica-chlorite-pyrite), propylitic type (chlorite-calcite-silica), and argillic type (kaolinit-ilit-smectite-chlorite-silica). Mineralization at Mount Pongkor has four stages infilling veins (Milesi, 1999), but in the study area only two stages of infilling are found, namely CQ facies and MOQ facies. CQ facies has content of 1.96 ppm for Au and 13.5 ppm for Ag, while the MOQ facies has 15.41 ppm for Au and 73.96 ppm for Ag. The vein texture are found in the form of primary growth texture (Colloform Band, Comb, Crustiform Band, Vuggy Quartz, and Massive Chalcedonic) and replacement texture (lattice bladed, parallel bladed, and saccharoidal). Based on these characteristics, it can be concluded that the type of deposit is low sulfidation epithermal deposit.